Gold Nanoparticles in Disulfide Based Polymer Matrices: Size, Structure and Responsivity - Wagner, Maximilian; Krieger, Anja; Gröhn, Franziska (Macromolecular Chemistry and Physics, 2023)
A disulfide-based polymer is used as a template for the synthesis of gold nanoparticles. Three different syntheses are tested: The simultaneous formation of gold nanoparticles and the disulfide polymer (A), the loading of a disulfide polymer matrix with HAuCl4 and then reducing with hydrazine (B), and reducing HAuCl4 with hydrazine in the presence of a cross-linking thiol follows by oxidative coupling of another thiol to the previously formed structures via disulfide bond formation (C). The ratio of the water-insoluble pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) and the water-soluble acids mercaptopropionic acid or mercaptosuccinic acid (MPA or MSA) are varied. The resulting gold nanostructures differ significantly with respect to their synthesis reaching from isolated particles to networks and raspberry-like structures. Due to the formation of disulfide bonds during the syntheses, the response of the hybrid nanoparticles to UV light and ultrasound is investigated, showing a breakdown of micrometer-sized structures to 50 nm-sized hybrid structures in aqueous solution.
CRIS-Team Scopus Importer:2023-12-22
Keywords: gold nanoparticles; mechanophores; nanotemplating; organic–inorganic hybrid structures; self-assembly